Traditional Profession and Livelihood Strategies Of Bede Community in Bangladesh: A Sociological Study (Social Science Review, 2022)
Bede community is a racial ethnic minority and floating people in Bangladesh. They move from one place to another to carry out their business for earning. After hearing the term Bede, the things which first clicked in one’s mind is that women roaming in a village with bag of business products on their head and vociferating to attract people to whom they offer treatments (joint pain, toothache), sell products like, home utensils, trinket sand amulets, bangles, herbal medicines etc. They are member of an ethnic minority group with unique traditional culture and lifestyle and their behavioural pattern also has a distinctive character, unusual from the people of mainstream society. Generally, these groups of people are socially, economically, and politically excluded and they are severely deprived of all types of necessities. Often, they become victim of discrimination and racial violence and obviously they are the subject of human rights violations. In this paper, the researchers attempt to draw the traditional nature of livelihood pattern of Bede community of Bangladesh, their exclusion and vulnerable socio-economic status, their adaptability power with the worst situation. Furthermore, this paper states some recommendations towards government and NGO’s for giving legal and voluntary actions to ensure the rights of Bede people in Bangladesh that may impact to their holistic development.Social Science Review, Vol. 38(1), June 2021 Page 109-132